Compartmentalization of membrane trafficking, glucose transport, glycolysis, actin, tubulin and the proteasome in the cytoplasmic droplet/Hermes body of epididymal sperm. Issue 8 (August 2015) - Au, Catherine E.; Hermo, Louis; Byrne, Elliot; Smirle, Jeffrey; Fazel, Ali; Kearney, Robert E.; Smith, Charles E.; Vali, Hojatollah; Fernandez-Rodriguez, Julia; Simon, Paul H. G.; Mandato, Craig; Nilsson, Tommy; et al.
Abstract : Discovered in 1909 by Retzius and described mainly by morphology, the cytoplasmic droplet of sperm (renamed here the Hermes body) is conserved among all mammalian species but largely undefined at the molecular level. Tandem mass spectrometry of the isolated Hermes body from rat epididymal sperm characterized 1511 proteins, 43 of which were localized to the structure in situ by light microscopy and two by quantitative electron microscopy localization. Glucose transporter 3 (GLUT-3) glycolytic enzymes, selected membrane traffic and cytoskeletal proteins were highly abundant and concentrated in the Hermes body. By electron microscope gold antibody labelling, the Golgi trafficking protein TMED7/p27 localized to unstacked flattened cisternae of the Hermes body, as did GLUT-3, the most abundant protein. Its biogenesis was deduced through the mapping of protein expression for all 43 proteins during male germ cell differentiation in the testis. It is at the terminal step 19 of spermiogenesis that the 43 characteristic proteins accumulated in the nascent Hermes body.